Left superior vena cava with coronary sinus ostial atresia with retrograde flow - Thanigai Arasu; Komal Tamildasan; Ganapathy Krishnan Subramaniam; Dhruva Sharma; Srinath N Reddy (Journal of Clinical and Scientific Research)
The left superior vena cava (LSVC) develops when the left common cardinal vein and the caudal part of the left superior cardinal vein fail to regress. We present a case where LSVC was associated with a bridging vein and coronary sinus ostial atresia. The dilated coronary sinus, which is the usual echocardiographic indicator of LSVC, is absent in this scenario. A 14 month old boy with tetralogy of Fallot underwent intracardiac repair; he was noticed to have a small LSVC; it was snared in order to proceed with surgery. During delivery of antegrade cardioplegia, there was resistance, the right atrium was opened immediately and coronary sinus ostium was found to be atretic. The snare around the LSVC was immediately released which enabled the delivery of further cardioplegia. The LSVC was then snared after cardioplegia delivery, and the intracardiac repair was done. The heart recovered in sinus rhythm, and the child was shifted with moderate inotropic support. Post-operative epicardial echocardiography confirmed retrograde flow in the LSVC from the coronary sinus to the innominate vein. LSVC with coronary sinus ostial atresia, although rare, should be recognised by the presence of retrograde flow in the LSVC. This could have significant implications for cardioplegia delivery and myocardial protection. Ligation or division of LSVC should not be done in the presence of retrograde flow in the vein with a small coronary sinus.